Racial, skin tone, and sex disparities in automated proctoring software - Yoder-Himes, Deborah R.; Asif, Alina; Kinney, Kaelin; Brandt, Tiffany J.; Cecil, Rhiannon E.; Himes, Paul R.; Cashon, Cara; Hopp, Rachel M. P.; Ross, Edna (Frontiers in Education, 2022)
Students of color, particularly women of color, face substantial barriers in STEM disciplines in higher education due to social isolation and interpersonal, technological, and institutional biases. For example, online exam proctoring software often uses facial detection technology to identify potential cheating behaviors. Undetected faces often result in flagging and notifying instructors of these as 'suspicious' instances needing manual review. However, facial detection algorithms employed by exam proctoring software may be biased against students with certain skin tones or genders depending on the images employed by each company as training sets. This phenomenon has not yet been quantified nor is it readily accessible from the companies that make this type of software. To determine if the automated proctoring software adopted at our institution and which is used by at least 1,500 universities nationally, suffered from a racial, skin tone, or gender bias, the instructor outputs from ~357 students from four courses were examined. Student data from one exam in each course was collected, a high-resolution photo was used to manually categorize skin tone, and the self-reported race and sex for each student was obtained. The likelihood that any groups of students were flagged more frequently for potential cheating was examined. The results of this study showed a significant increase in likelihood that students with darker skin tones and Black students would be marked as more in need of instructor review due to potential cheating. Interestingly, there were no significant differences between male and female students when considered in aggregate but, when examined for intersectional differences, women with the darkest skin tones were far more likely than darker skin males or lighter skin males and females to be flagged for review. Together, these results suggest that a major automated proctoring software may employ biased AI algorithms that unfairly disadvantage students. This study is novel as it is the first to quantitatively examine biases in facial detection software at the intersection of race and sex and it has potential impacts in many areas of education, social justice, education equity and diversity, and psychology.